The Influence of Motivation on Employee Performance - Ria Festiningtyas; Alini Gilang (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
Human resources are people working in a company and have the same functions and can be quantified (quantitative), and human resources is a major factor because the success and failure of a company then depend on its human resources. This research was taking place at PT. Telekomunikasi Witel Lembong Bandung, Lembong street No. 11-13, Bandung, West Java. The purpose of this study was to determine the effect of motivation on employee performance at PT. Telekomunikasi Indonesia Witel Lembong Bandung. This research uses a quantitive research method with the type of causal descriptive. The research data collected by the questionnaire to 70 employees. The sampling technique in this research is probability sampling with a simple random sampling technique then the data is processed by descriptive analysis and simple linear regression analysis. Based on the result of this research it can be concluded that the responses of respondents to motivation variables get the value of 82,9% in the “high” category, and employee performance variables get the value of 83,5% where the percentage is in the “high” category. Motivation positively and significantly affect the performance of the employee of PT. Telekomunikasi Witel Lembong Bandung amounted to 39,5%.